1987
DOI: 10.1159/000248870
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Retinoid Therapy Is Needed for Maintenance of Cancer Chemopreventive Effect

Abstract: Two patients with multiple basal cell carcinomas, due either to the nevoid basal cell carcinoma syndrome (NBCCS) or arsenical insecticide exposure, were treated with oral isotretinoin for 7 or 8 years, respectively. Gradually decreasing dosage levels were employed. During the initial courses of therapy, high doses (2.0–3.0 mg/kg/day) were intended as chemotherapy. In these patients only 6 of 40 (15%) lesions underwent complete clinical regression. In subsequent courses aimed at chemoprevention, the dose was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Human studies in which withdrawal of oral retinoids generally resulted in a rapid recurrence of tumors are consistent with an inhibitory effect on promotion and progression rather than on initiation (14). Tazarotene inhibited the formation of the majority of microscopic BCCs and reduced BCC size, suggesting that it is effi- Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Human studies in which withdrawal of oral retinoids generally resulted in a rapid recurrence of tumors are consistent with an inhibitory effect on promotion and progression rather than on initiation (14). Tazarotene inhibited the formation of the majority of microscopic BCCs and reduced BCC size, suggesting that it is effi- Fig.…”
Section: Discussionmentioning
confidence: 72%
“…A great deal of work has been done evaluating the chemotherapeutic and/or chemopreventive effects of retinoids on BCCs. 40,41 These effects are thought to be mediated via binding to the corresponding intranuclear receptors, retinoic acid receptors (RAR) -␣, -␤, and -␥. Recently, it has been demonstrated that VDR require heterodimerization with auxiliary proteins for effective DNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, long-term therapy with low doses of systemic retinoids such as isotretinoin/ATRA and 13-cis retinoic acid, was not effective in reducing the occurrence of BCCs at new sites in patients with previously reported small numbers (1, 2) of BCCs (31). The differences between our observations and those observed for skin cancer patients treated with systemic retinoids may be (a) mode of delivery: topical tazarotene application may result in more retinoid reaching the tumor cells; (b) type of retinoid: the human studies were carried out using other pan-RAR agonists (that is, 13-cis retinoic acid and ATRA); from our observations, the outcome of activating different RARs in the skin may be quite different; (c) there may be a species difference in the response to retinoids; and/or (d) the sustained and curative effects of tazarotene applied topically may be specific to microscopic BCCs; previous observations showed that systemic retinoids prevented the occurrence of new BCCs in BCNS patients during therapy but had no effect against the majority of existing BCCs in these patients (10). However, reports that topical tazarotene application cures 30% to 50% of visible human BCCs (13) and our data suggest that topical tazarotene effectively cures both microscopic and macroscopic BCCs in contrast to the above-mentioned systemically used retinoids.…”
Section: Discussionmentioning
confidence: 68%
“…to human studies in which new BCCs promptly appear after systemic retinoids are stopped in BCNS and XP patients (10,11). Also, long-term therapy with low doses of systemic retinoids such as isotretinoin/ATRA and 13-cis retinoic acid, was not effective in reducing the occurrence of BCCs at new sites in patients with previously reported small numbers (1, 2) of BCCs (31).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation